2021
DOI: 10.1161/jaha.121.023394
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions and Mortality Among Fee‐for‐Service Medicare Patients With Minor Stroke or Transient Ischemic Attack: Findings From the COMPASS Cluster‐Randomized Pragmatic Trial

Abstract: Background Mortality and hospital readmission rates may reflect the quality of acute and postacute stroke care. Our aim was to investigate if, compared with usual care (UC), the COMPASS‐TC (Comprehensive Post‐Acute Stroke Services Transitional Care) intervention (INV) resulted in lower all‐cause and stroke‐specific readmissions and mortality among patients with minor stroke and transient ischemic attack discharged from 40 diverse North Carolina hospitals from 2016 to 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…16 More recently, a randomized trial focused on effective TOC showed that the intervention was inconsistently implemented, with no effect on functional outcome or readmission. 17,18 Some explanations proposed for this negative result include that hospitals had difficulty sustaining the intervention, there was significant loss to follow-up, and outcome measures may have been insensitive in a milder stroke population. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 More recently, a randomized trial focused on effective TOC showed that the intervention was inconsistently implemented, with no effect on functional outcome or readmission. 17,18 Some explanations proposed for this negative result include that hospitals had difficulty sustaining the intervention, there was significant loss to follow-up, and outcome measures may have been insensitive in a milder stroke population. 19…”
Section: Discussionmentioning
confidence: 99%
“…16 More recently, a randomized trial focused on effective TOC showed that the intervention was inconsistently implemented, with no effect on functional outcome or readmission. 17,18 Some explanations proposed for this negative result include that hospitals had difficulty sustaining the intervention, there was significant loss to follow-up, and outcome measures may have been insensitive in a milder stroke population. 19 Nonetheless, we posit that a detailed understanding of the associations and drivers behind poor adoption of important posthospitalization behaviors, as we have described in the current analysis, is important to inform interventions, identify high-risk patients, and direct limited healthcare resources to these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…27 It is important to note, however, that the COMPASS intervention, as delivered, did not impact readmission rates or patients' functional status, despite the increased rate of ambulatory visits relative to usual care. 10,28 Additional research identifying effective models of cooperative and coordinated post-acute stroke care is therefore needed.…”
Section: Discussionmentioning
confidence: 99%
“…The average readmitted inpatient cost per person was $12,000 between 2008 and 2013 5. Some of the costs are avoidable because more than 50% of readmissions for patients with stroke and other cerebrovascular diseases are considered preventable 14,15…”
mentioning
confidence: 99%
“…5 Some of the costs are avoidable because more than 50% of readmissions for patients with stroke and other cerebrovascular diseases are considered preventable. 14,15 Practical requirements for ongoing care are addressed and provided upon hospital discharge to patients with stroke in order to prevent complications, avoidable readmissions, and recurrent stroke. To reduce readmission rates, current literature supports a variety of successful pre-and postdischarge interventions including discharge planning, patient education, followup telephone calls, home visits, and transition coaching.…”
mentioning
confidence: 99%